2017
DOI: 10.1287/mnsc.2016.2505
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Stereotypes of Risk Preferences: Experimental Evidence from a Matrilineal and a Patrilineal Society

Abstract: W e use a controlled experiment to analyze gender differences in stereotypes about risk preferences of men and women across two distinct island societies in the Pacific: the patrilineal Palawan in the Philippines and the matrilineal Teop in Papua New Guinea. We find no gender differences in actual risk preferences, but we find evidence for culture-specific stereotypes. Like men in Western societies, Palawan men overestimate women's actual risk aversion. By contrast, Teop men underestimate women's actual risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…While there is a difference in the mean risk preference of men and women in our sample, our subjects assigned the role of managers behave as if this difference were much larger. Our result is also consistent with Pondorfer et al (2017), who find that (despite no actual difference in risk preferences relative to men in their sample) men underestimate women's risk preferences in a patrilineal society, as well as with the finding in Dargnies (2012) that men do not avoid competition to punish “undeserving” low performers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While there is a difference in the mean risk preference of men and women in our sample, our subjects assigned the role of managers behave as if this difference were much larger. Our result is also consistent with Pondorfer et al (2017), who find that (despite no actual difference in risk preferences relative to men in their sample) men underestimate women's risk preferences in a patrilineal society, as well as with the finding in Dargnies (2012) that men do not avoid competition to punish “undeserving” low performers.…”
Section: Resultssupporting
confidence: 92%
“…While there is a difference in the mean risk preference of men and women in our sample, our subjects assigned the role of managers behave as if this difference were much larger. Our result is also consistent with Pondorfer et al (2017), who find that (despite no actual Note: Cells in columns labeled (1) and ( 2) represent the percentage of managers who chose to compete on behalf of their direct reports in our experiment under the no information and information treatments. The simulated results are the estimated percentages of managers entering into competition for direct reports using the actual distributions of performance and risk preferences in our experimental sample.…”
Section: Managers' Discrimination When Earning For Otherssupporting
confidence: 90%
See 1 more Smart Citation
“…For example, several studies on financial behavior find that women are more risk-averse than men (Bernasek and Shwiff, 2001; Olsen and Cox, 2001; Gerxhani, 2007; Maxfield et al , 2010; Charness and Gneezy, 2012; Gibson et al , 2013; Lohse and Qari, 2014; Montford and Goldsmith, 2016; D’Attoma et al , 2017). On the contrary, other studies have not found strong evidence that gender is a significant predictor of financial risk tolerance (Feng and Seasholes, 2008; Bucciol et al , 2013; Chu et al , 2015; Pondorfer et al , 2016). In addition, the difference in risk tolerance cannot be explained only by gender itself but it is sensitive to other demographic variables such as income, education and marital status.…”
Section: Background Literature and Hypotheses Developmentmentioning
confidence: 73%
“…Research across psychology (Arch, 1993;Byrnes et al, 1999), decision-making (Jianakoplos and Bernasek, 1998;Halko et al, 2012;Charness and Gneezy, 2012) and entrepreneurial risk-taking (Masters and Meier, 1988;Sexton and Bowman-Upton, 1990) consistently suggests that women exhibit higher risk aversion tendencies than men, particularly regarding financial risk aversion (Jianakoplos and Bernasek, 1998). However, other studies do not find gender differences after controlling for items such as uncertainty (Sarin and Wieland, 2016), domain specificity/familiarity (Wieland and Sarin, 2012) and culture-specific stereotypes (Pondorfer et al, 2017).…”
Section: Risk Preferences and Framing Effectsmentioning
confidence: 99%